Identifying stress and coping behavior factors of ethnic minority workers in the construction industry via a focus group - Ahmed, Khursheed; Leung, Mei-yung; Li, Yueran (Journal of Civil Engineering and Management, 2024)
The construction industry is notorious for stressful jobs, particularly for ethnic minority construction workers (EM-CWs), who experience complicated issues in the host country. Despite the high-level stress of EM-CWs compared to native construction workers, the particular coping behaviors of EM-CWs is unclear. Due to their cultural differences, religious beliefs, and possible stigma related to sharing feelings, typical stress management strategies may not be effective in relieving the stress of EM-CWs. To manage the stress of EM-CWs and also to benefit organizational productivity, it is important to identify the specific coping behaviors adopted by EM-CWs in response to stress. Therefore, this study aims to explore the stress management factors of EM-CWs. Six focus group discussions were conducted, made up of five EM-CWs groups (three general worker groups and two skilled worker groups) and one group of foremen. Contextual analysis was used to analyze the focus groups’ qualitative data. The study identified 11 items of stress for EM-CWs in two major categories: emotional and physical stress. In addition to problem-focused (i.e., planned problem-solving, seeking instrumental support, and cognitive appraisal) and emotion-focused coping behaviors (i.e., seeking emotional support, emotional discharge, and escapism), the current study also explored religious-focused coping behaviors (i.e., religious practice, service, and meditation) of EM-CWs. The findings advance coping-behavior literature by addressing important features of religious coping behaviors in the construction industry. The study explored the unique stress management factors of EM-CWs, which can be used to manage the stress of EM-CWs, improve their stress management approaches, and design various stress management programs for EM-CWs. Furthermore, several recommendations were made in initiating time management training, encouraging organizations to consider mental health needs in the construction industry, acknowledging the specific cultural context of EM-CWs, striving to reduce the stigma around sharing emotions under stress, facilitating an adequate on-site environment to practice religion, and introducing mindfulness programs to relieve EM-CW stress and improve their performance.